PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP MOTIVASI BERWIRAUSAHA PADA SISWA SMA AL-HUDA PEKANBARU - Mesy Sasmita; Henny Indrawati; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study was to determine how much influence entrepreneurship education has on entrepreneurial motivation of class X and XI at SMA AL-Huda Pekanbaru. The data needed in this study are primary data collected by questionnaire. The study population was all students of class X and XI IPS SMA AL-Huda Pekanbaru as many as 116 students. The samples taken were 90 students based on the Slovin formula with proportional random sampling techniques used were descriptive analysis and simple linear regression. The result showed that entrepreneurship education had an effect on the entrepreneurial motivation of class X and XI students at SMA AL-Huda Pekanbaru by 0.422. This means that the level of entrepreneurship education has an impact on entrepreneurial motivation. The higher the entrepreneurship education, the higher the student’s entrepreneurial motivation. The r square value is 0.216 which indicates that the entrepreneurship education variable can be explained by the entrepreneurial motivation variable by 21.6%, while the remaining 78.4% is explained by other factors not examined in this study, namely internal factors, intelligence, level education.Key Words: Entrepreneurship Education, Entrepreneurial Motivation